PENGARUH KUALITAS PELAYANAN POSPAY TERHADAP KEPUASAN PELANGGAN PADA POS INDONESIA DENPASAR - Olgina, Aulya; Wirantari, I Dewa Ayu Putri; Yudartha, Putu Dharmanu (CITIZEN CHARTER, 2024)
Technology and information play such a crucial part in modern life that they influence the quality of every community service. Users are more likely to be happy with a service if they can utilize it quickly and simply to get what they need. The goal of this research was to find out how the quality of Pospay service at Pos Indonesia Denpasar affects the happiness of their customers. The purpose of this study is to quantify the impact that Pos Indonesia Denpasar's service quality has on their customers' overall happiness. One hundred clients of Pos Indonesia Denpasar were surveyed using questionnaires to collect primary data for this research. Statistical analysis revealed that the quality of Pospay service has an influence on the satisfaction of Pos Indonesia Denpasar customers, with a t count of 8.854 being bigger than the t table of 1.984 at a significance level of 0.000.   Kata Kunci : Service Quality, Customer Satisfaction, Pospay, PT Pos Indonesia Denpasar